Epistemologi Dan Metodologi Tafsir Dalam Tarjumān Al-Mustafīd Karya ‘Abd Al-Ra’ūf Al-Singkilī Sebagai Model Lokalisasi Intelektual Islam Nusantara - Enep Syamsudin; Suryaman; Zakaria, Aceng (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Tarjumān al-Mustafīd by ‘Abd al-Ra’ūf al-Singkilī is a monumental milestone in Islamic historiography, widely recognized as the first complete 30-chapter (juz) exegesis written in the Malay language using Jawi script in Southeast Asia. This library research, centered on textual analysis and intellectual history, aims to deconstruct al-Singkilī’s hermeneutical methodology and map the epistemological framework of 17th-century Nusantara exegesis by synthesizing contemporary academic literatures. The findings demonstrate that the cognitive structure of Tarjumān al-Mustafīd is anchored in the concept of